Importance of Capacity Building Programme for Science Academic in Tertiary Institutions in Nigeria (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The paper examined the importance of providing effective capacity building programme for science academic in the tertiary institutions in Nigeria. The study concluded these capacity building programs play a crucial role in enhancing the knowledge, skills, improvement in job performance, quality education delivery, collaboration, research and innovation development, attraction of top academic, innovation and innovative teaching methods and research development and ultimately contributing to the overall quality of education in the country. Based on this finding, the paper recommends that TETFUND an agency of federal government of Nigeria in charging of facility development, research and staff training in tertiary institutions should increase the allocation for staff development in tertiary institutions especially for science academic. Private institutions and international organizations should support the tertiary institutions in Nigeria in the rea of provision of capacity building programme to enhance the job performance of the academic staff.